Challenges in Analytical Quality Assurance - Reichenbächer, Manfred (Springer Berlin Heidelberg Imprint: Springer, 2011)
Working in the lab, but unsure what your results actually mean? Would you like to know how to apply trueness tests, calculate standard deviations, estimate measurement uncertainties or test for linearity? This book offers you a problem-based approach to analytical quality assurance (AQA). After a short introduction into required fundamentals, various topics such as statistical tests, linear regression and calibration, tool qualification or method validation are presented in the form of exercises for self-study. Solutions are provided in a clear step-by-step manner. Interactive Excel-sheets are available as Extra Materials for trying out the various concepts. For professionals as well as graduate students confronted with analytical quality assurance for the first time, this book will be the clue to meeting such challenges.